(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
A novel epidemic SEIR model with distributed delay on scale-free network is proposed in this paper. The formula of the basic reproduction number R_0 for the model is given, and globally dynamic behaviours of the model are discussed. Numerical simulations are carried out to demonstrate the main results.